2020
DOI: 10.1177/0706743720970860
|View full text |Cite|
|
Sign up to set email alerts
|

The Canadian Network for Mood and Anxiety Treatments (CANMAT) Task Force Recommendations for the Use of Racemic Ketamine in Adults with Major Depressive Disorder: Recommandations Du Groupe De Travail Du Réseau Canadien Pour Les Traitements De L’humeur Et De L’anxiété (Canmat) Concernant L’utilisation De La Kétamine Racémique Chez Les Adultes Souffrant De Trouble Dépressif Majeur

Abstract: Objective: Patients with major depressive disorder often have limited response to first-line and second-line medications; hence, novel pharmacological treatments are needed for treatment-resistant depression (TRD). Ketamine, an N-methyl-d-aspartate (NMDA) receptor antagonist, has demonstrated rapid antidepressant effects in patients with TRD. The Canadian Network for Mood and Anxiety Treatments (CANMAT) convened a task force to review the evidence for efficacy and safety of racemic ketamine and to provide reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 99 publications
(125 reference statements)
0
41
0
3
Order By: Relevance
“…Μόνο σε μία μειονότητα ασθενών παρατηρείται σταθερή βελτίωση με διάρκεια 30 ημερών ή και περισσότερο. [15][16][17][18] Σε κάθε περίπτωση πάντως η αντικαταθλιπτική δράση της κεταμίνης εξασθενεί ύστερα από μία μεμονωμένη χορήγηση, ενώ τα αποτελέσματα της επαναλαμβανόμενης χορήγησής της δεν έχουν ακόμη μελετηθεί επαρκώς. 15,16,19 Στο μεταξύ, άλλα προκλινικά δεδομένα προερχόμενα από ζωικά μοντέλα της κατάθλιψης υποδεικνύουν ότι το (R)-εναντιομερές της κεταμίνης [(R)-κεταμίνη], είναι δυνατόν να παρουσιάζουν μεγαλύτερη διάρκεια δράσης και λιγότερες ανεπιθύμητες ενέργειες σε σύγκριση με την (R, S)-κεταμίνη και την εσκεταμίνη.…”
Section: διπολική κατάθλιψηunclassified
See 2 more Smart Citations
“…Μόνο σε μία μειονότητα ασθενών παρατηρείται σταθερή βελτίωση με διάρκεια 30 ημερών ή και περισσότερο. [15][16][17][18] Σε κάθε περίπτωση πάντως η αντικαταθλιπτική δράση της κεταμίνης εξασθενεί ύστερα από μία μεμονωμένη χορήγηση, ενώ τα αποτελέσματα της επαναλαμβανόμενης χορήγησής της δεν έχουν ακόμη μελετηθεί επαρκώς. 15,16,19 Στο μεταξύ, άλλα προκλινικά δεδομένα προερχόμενα από ζωικά μοντέλα της κατάθλιψης υποδεικνύουν ότι το (R)-εναντιομερές της κεταμίνης [(R)-κεταμίνη], είναι δυνατόν να παρουσιάζουν μεγαλύτερη διάρκεια δράσης και λιγότερες ανεπιθύμητες ενέργειες σε σύγκριση με την (R, S)-κεταμίνη και την εσκεταμίνη.…”
Section: διπολική κατάθλιψηunclassified
“…[15][16][17][18] Σε κάθε περίπτωση πάντως η αντικαταθλιπτική δράση της κεταμίνης εξασθενεί ύστερα από μία μεμονωμένη χορήγηση, ενώ τα αποτελέσματα της επαναλαμβανόμενης χορήγησής της δεν έχουν ακόμη μελετηθεί επαρκώς. 15,16,19 Στο μεταξύ, άλλα προκλινικά δεδομένα προερχόμενα από ζωικά μοντέλα της κατάθλιψης υποδεικνύουν ότι το (R)-εναντιομερές της κεταμίνης [(R)-κεταμίνη], είναι δυνατόν να παρουσιάζουν μεγαλύτερη διάρκεια δράσης και λιγότερες ανεπιθύμητες ενέργειες σε σύγκριση με την (R, S)-κεταμίνη και την εσκεταμίνη. Παρόμοια πλεονεκτήματα πιθανώς να έχει και η (S)-νορκεταμίνη, με ενδεχομένως ίση αντικαταθλιπτική ισχύ και ταχύτητα έναρξης δράσης με την κεταμίνη και την εσκεταμίνη αλλά με ένα καλύτερο βιοχημικό προφίλ και λιγότερες ανεπιθύμητες ενέργειες από την ψυχική σφαίρα.…”
Section: διπολική κατάθλιψηunclassified
See 1 more Smart Citation
“…The Canadian Network for Mood and Anxiety Treatments (CANMAT) Task Force recently provided recommendations for the use of racemic ketamine ( R,S )-ketamine in adults with treatment-resistant depression (TRD). 1 Briefly, the guidelines noted Level 1 evidence for the efficacy of acutely administered intravenous (IV) ( R,S )-ketamine in adults with TRD but suggested that this intervention be reserved as a third-line recommendation. In addition, the guidelines noted Level 3 evidence for using ( R,S )-ketamine as continued or ongoing maintenance treatment and recommended that it be used on a case-by-case basis.…”
mentioning
confidence: 99%
“…Ketamine is a racemic mixture, composed of equal amounts of (S)-ketamine and (R)-ketamine. From the early studies, which showed a rapid onset of antidepressant action, the intravenous infusion of the racemic mixture of ketamine is now a recommended treatment in some countries (Swainson et al, 2020). Janssen have developed a nasally administered formulation of (S)-ketamine, which has been approved as a medicine for treatment-resistant depression in the USA and more recently in Europe (Mahase, 2019).…”
mentioning
confidence: 99%